2016
DOI: 10.3923/pjbs.2016.65.70
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Uncover Cryptic Diversity in Goat Fishes (Family: Mullidae) Across the Egyptian Coastal Waters

Abstract: Despite ongoing efforts to protect species and ecosystems in the egyptian costs of the Red Sea and Mediterranean Sea, habitat degradation, overfishing and pollution have posed serious challenges to marine natural resources. In spite of the accumulated knowledge on the systematics of commercial fishes in Egypt recent results suggested that we are far from having a complete picture of egyptian fish diversity. The accurate identification of species is a very important component in many fields of biological resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For instances, in several studies, more than 98% of the analyzed species were clearly identified using DNA barcoding approach (Costa et al, 2012;deWaard, Hebert, & Humble, 2011;Liu & Zhang, 2018;Steinke, Zemlak, & Hebert, 2009;Valdez-Moreno, Ivanova, Elías-Gutiérrez, Contreras-Balderas, & Hebert, 2009;Ward, Zemlak, Innes, Last, & Hebert, 2005;Zhang & Hanner, 2011). Studies have also documented the usefulness of DNA barcoding approach in unraveling cryptic lineages within many species of fish (Benzaquem, Oliveira, da Silva Batista, Zuanon, & Porto, 2015;Mat Jaafar, Taylor, Mohd Nor, de Bruyn, & Carvalho, 2012;Mohammed, Manal, Rasha, & Magdy, 2016). Thus, DNA barcoding could be an effective genetic tool that would assist Nigerian conservation managers in identifying species accurately and uncover hidden diversity.…”
Section: Introductionmentioning
confidence: 99%
“…For instances, in several studies, more than 98% of the analyzed species were clearly identified using DNA barcoding approach (Costa et al, 2012;deWaard, Hebert, & Humble, 2011;Liu & Zhang, 2018;Steinke, Zemlak, & Hebert, 2009;Valdez-Moreno, Ivanova, Elías-Gutiérrez, Contreras-Balderas, & Hebert, 2009;Ward, Zemlak, Innes, Last, & Hebert, 2005;Zhang & Hanner, 2011). Studies have also documented the usefulness of DNA barcoding approach in unraveling cryptic lineages within many species of fish (Benzaquem, Oliveira, da Silva Batista, Zuanon, & Porto, 2015;Mat Jaafar, Taylor, Mohd Nor, de Bruyn, & Carvalho, 2012;Mohammed, Manal, Rasha, & Magdy, 2016). Thus, DNA barcoding could be an effective genetic tool that would assist Nigerian conservation managers in identifying species accurately and uncover hidden diversity.…”
Section: Introductionmentioning
confidence: 99%
“…While morphology-based taxonomy might possibly overlook such diversity, DNA barcoding, involving mitochondrial cytochrome c oxidase subunit I (COI), has been recommended as a complementary taxonomic tool for species identification and unravelling cryptic diversity 6 . The COI barcoding has proven successful in the identification of fish species [1][2][3][4][5]7 and the discovery of cryptic diversities 2,[8][9][10][11] . Several examples of deep COI sequence divergences within fish species have been attributed to cryptic speciation 2,3,[8][9][10][11] .…”
mentioning
confidence: 99%
“…Lessepsian invaders; see Bernardi et al, 2016), which includes U. moluccensis. The ecological differences between the Red Sea and Mediterranean Sea might explain the genetic variance of invader goatfish species from the Red Sea to the Mediterranean Sea through the Suez Canal (Ahmed et al, 2016). However, some Lessepsian species might have been introduced from the Red Sea by alternative pathways, such as anthropogenic transport (e.g.…”
Section: Discussionmentioning
confidence: 99%